Effect of instrumental music on anxiety and depression among hemodialysis patients: A randomized controlled trial - Mohammad Imani; Amir Jalali; Nader Salari; Parvin Abbasi (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Hemodialysis patients suffer from mental disorders such as anxiety and depression. One of the known nonpharmacological methods to eliminate these disorders is music therapy. The present study aimed to investigate the effect of instrumental music on state depression and anxiety in hemodialysis patients. MATERIALS AND METHODS: This study was a clinical trial. The population was hemodialysis patients in Hamedan in 2017 and 50 patients were selected and randomly divided into experimental and control groups. The duration each time of the instrumental music intervention for the experimental group was 3 weeks, 3 times a week for 20 min. Data were measured by beck depression inventory and SpeilBerger State-Trait Anxiety Inventory-Y1 before the intervention and immediately after the last intervention and analyzed using Yates correction, Chi-square test, Mann-Whitney U-test, independent t-test, and Wilcoxon test. RESULTS: No significant difference between the intervention and control groups was observed before the study in terms of demographic variables (P > 0.05). In the intervention group, the mean and standard deviation of the depression score before the intervention was 8.99 ± 23.68 and after the intervention reached 7.54 ± 14.88, which shows that the variable was significant (P = 0.001); however, no significant difference was observed in the control group. In the intervention group, the mean of state anxiety before the intervention was 10.05 ± 53.76 and after the intervention reached 9.76 ± 42.48, which was statistically significant (P = 0.004), while no significant difference was observed in the control group. CONCLUSION: The results indicate the positive effect of instrumental music on reducing anxiety and depression in hemodialysis patients. It is recommended that this therapy be used as a nursing method to reduce state anxiety and depression in hemodialysis patients.